Implementation of cites (convention on international trade in endangered species of wild fauna and flora) in dealing with illegal timber trade in Indonesia - Siba, M. Angela Merici; Mbiri , Adeodata L.C.B. (Institute Of computer Science (IOCS), 2025)
This research examines the implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora in dealing with illegal timber trade in Indonesia. As a convention, CITES helps Indonesia deal with the illegal timber trade by making rules for timber traders. The problem of illegal logging and timber trade is a global crime. This action has damaged forests and even caused extinction for wildlife due to illegal logging for the benefit of certain groups. In this research, the author uses the literature study method by collecting information from reading which is then analyzed to get results. The purpose of this research is to find out the implementation of CITES in Indonesia in dealing with illegal timber trade that causes forest damage and loss. From the results of the study it can be found that Indonesia has ratified CITES and implemented it in the form of laws and Ministerial regulations. CITES is an international treaty that deals with plant and animal trade. Every country that ratifies CITES must be able to trade legally. By ratifying and making rules in Indonesia, timber trade can be carried out legally and pay attention to various aspects related to the environment. The implementation of CITES has an impact on forest protection, people can trade timber legally and protect animals in the forest.